2005
DOI: 10.1161/01.atv.0000157582.33180.a9
|View full text |Cite
|
Sign up to set email alerts
|

Stent-Based Delivery of Tissue Inhibitor of Metalloproteinase-3 Adenovirus Inhibits Neointimal Formation in Porcine Coronary Arteries

Abstract: Background-Stent-based antiproliferative therapy appears to decrease in-stent restenosis. However, alternative approaches might produce equivalent efficacy with better long-term safety. In previous work, an adenovirus capable of expressing the tissue inhibitor of metalloproteinase-3 (RAdTIMP-3) inhibited neointima formation in cell cultures and porcine saphenous vein grafts. RAdTIMP-3 decreased smooth muscle cell migration, stabilized the extracellular matrix, and uniquely promoted apoptosis. The current study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 39 publications
(32 reference statements)
0
50
0
1
Order By: Relevance
“…Indeed, approaches that target the inhibition of VSMC proliferation have been found to be more promising in arresting the development of neointima. [11][12][13][14] Toward elucidation of signal transduction mechanisms that are ubiquitously involved in the mitogenic actions of various VSMC agonists, we have shown previously that both receptor tyrosine kinase (RTK) and G protein-coupled receptor (GPCR) agonists such as platelet-derived growth factor-BB (PDGF-BB) and thrombin, respectively, activate nuclear factor of activated T cells (NFATs) and signal transducer and activator of transcription-3 (STAT-3) in stimulating VSMC growth and/or motility. 9,[15][16][17][18] Early studies from various laboratories have shown that STATs play an important role in the regulation of cytokineinduced gene expression.…”
mentioning
confidence: 99%
“…Indeed, approaches that target the inhibition of VSMC proliferation have been found to be more promising in arresting the development of neointima. [11][12][13][14] Toward elucidation of signal transduction mechanisms that are ubiquitously involved in the mitogenic actions of various VSMC agonists, we have shown previously that both receptor tyrosine kinase (RTK) and G protein-coupled receptor (GPCR) agonists such as platelet-derived growth factor-BB (PDGF-BB) and thrombin, respectively, activate nuclear factor of activated T cells (NFATs) and signal transducer and activator of transcription-3 (STAT-3) in stimulating VSMC growth and/or motility. 9,[15][16][17][18] Early studies from various laboratories have shown that STATs play an important role in the regulation of cytokineinduced gene expression.…”
mentioning
confidence: 99%
“…The potency of TIMP-1 as a therapeutic gene for antineointimal hyperplasia has been verified in various animal models (47,48). Johnson et al (48) found that stent-based delivery of TIMP-3 adenovirus inhibits neointimal formation in porcine coronary arteries (48). Downregulation of platelet-derived growth factor-β receptor expression and upregulation of plasminogen activator inhibitor-1 and light-type caldesmon, a potent cytostatic and antiangiogenic protein, using a gene targeting and adenoviral gene transfer approach, has also been found to inhibit neointima formation (49).…”
Section: Antineointimal Hyperplasiamentioning
confidence: 99%
“…Although early studies using marimastat, a broad-spectrum MMP inhibitor, showed significantly reduced neointimal formation in cultured human saphenous vein graft segments, the potential of marimastat as an antimetastatic agent was halted at phase III due to a lack of efficacy and dose-limiting toxicity (46). The potency of TIMP-1 as a therapeutic gene for antineointimal hyperplasia has been verified in various animal models (47,48). Johnson et al (48) found that stent-based delivery of TIMP-3 adenovirus inhibits neointimal formation in porcine coronary arteries (48).…”
Section: Antineointimal Hyperplasiamentioning
confidence: 99%
“…Следовательно, стабилизация внеклеточного ма-трикса может служить ограничением миграции ГМК к неоинтиме. В соответствии с этой идеей Johnson и его коллеги [30] полностью иммоби-лизировали суспензию Ad-вектора, кодирующего синтез тканевого ингибитора металлопротеина-зы-3 (TIMP3), на стенты из нержавеющей стали с полифосфорилхолиновым покрытием. На 28-е сутки после имплантации стента в сонные арте-рии свиньи объем неоинтимы был уменьшен на 40 и 50 % у животных с Ad-TIMP3-выделяющими стентами по сравнению со свиньями, которым были установлены НМС [30].…”
Section: гены ингибирующие пролиферацию и миграцию гладкомышечных клunclassified